A Preliminary Inventory and Management Plan for Medicinal Plant Conservation Areas at Amgaon and Kakati in Belgaum District of Karnataka - Hegde, Harsha V.; Upadhya, Vinayak; Pai, Sandeep R.; Hegde, Gurumurthi R.; Hosur, Girish; Mesta, Divakar (Indian Forester, 2013)
Western Ghats of India hosts several medicinal plants that are endemic to the area. Same is true with Karnataka, which is endowed with natural biological wealth. During present study medicinal plants in the proposed MPCA at Amgaon and Kakati range of Belgaum division were documented with an objective to develop strategies for their conservation. Total of 130 plant species were recorded at Amgaon and 66 sprcies at Kakati MPCA, out of which about 82% and 70% respectively were found to be of medicinal importance.